TINJAUAN KESANTUNAN BERBAHASA DALAM IJAB DAN SYAIR SAWER PADA UPACARA NGAROT - Ade Mulyanah (Jurnal Sosioteknologi, 2011)
This paper is a qualitative study using descriptive methods. The purpose of paper provides an overview of civility and poetic language in the "Sawer" consent ngarot at the ceremony.The ceremony is a ceremony in the District of Ngarot, Sumedang. Sumedang is one of regencies in West Java. In this district, precisely in the Village Karedok, the District of Teak Gede, there are traditional ceremonies called "ngarot". "Ngarot" in Javanese word means banquet before working on the fields, whereas in Sundanese, ngarot is said to derived from "ngaruat", the word that means salvation for refusing reinforcements. There are several stages in the ceremony ngarot. However, the author discusses only part of the ceremony on the consent and "Sawer". The expression on the consent and "Sawer" is studied based on the form of politeness and speech act. The results showed (1) decency language as reflected in the second stage of the ceremony shows the dominance of sympathy maxim 'Sympathy maxim "who expressed the hope that is positive, (2) forms of speech in the answer to prayer and "Sawer" poetry is (1) ilokusi strict / directive forms of speech decades ulah'awas do '), (2) power ilokusi expressed in particular words, and (3) ilokusi using wordplay. Key words: ceremony ngarot, maxims, ilokusi, speech act